A1.48 Enhanced expression of CD11c on non-classical CD16+ peripheral blood monocytes in early rheumatoid arthritis. (31st January 2014) - Krystufkova, Olga; Mann, Herman; Hulejova, Hana; Senolt, Ladislav; Vencovsky, Jiri
Abstract : Background and Objectives: Classical (CM), non-classical (NCM) and intermediate populations of human monocytes are characterised by differential expression of CD14 and CD16. NCM and IM are potent antigen presenting cells and producers of pro-inflammatory cytokines. They are enriched in patients with established rheumatoid arthritis (RA) and their numbers correlate with disease activity and response to therapy with methotrexate (MTX) and glucocorticoids (GCS). CD11c plays a role in antigen presentation and production of pro-inflammatory cytokines. Increased expression of CD11c on mononuclear blood cells and a predictive role of higher CD11c mRNA expression for response to TNFα blocking treatment in RA were described. We evaluated the expression of CD11c on monocyte subpopulations in patients with early rheumatoid arthritis (ERA) and its changes after three months of treatment with GCS and non-biological disease modifying drugs. Materials and Methods: 29 patients with ERA and 10 gender and age-matched healthy controls (HC) were included in this study. ERA patients had symptom duration for <6 months and fulfilled the 2010 ACR/EULAR classification criteria for RA. Disease activity was assessed using DAS28. Monocyte subpopulations were defined according to IUIS nomenclature (CM:CD14 + CD16 -, NCM:CD14 dim CD16 ++ ) using multicolour flow cytometry. Based on isotype and FMO controls for CD14 and CD16; two intermediate (IM) populations were evaluated (CD14 + CD16 dim and CD14 + CD16 ++ ). CD11c expression was analysed by median fluorescence intensity. Results: Expansion of both intermediate populations (IM-CD16 dim, p<0.001; IM-CD16 ++, p = 0.02) and reduction of CM (p<0.0001) were demonstrated in ERA patients compared to HC. NCM displayed enhanced expression of CD11c compared to CM and to both IM subpopulations (p<0.001). Compared to HC, the expression of CD11c was significantly higher in both NCM (p = 0.04) and CM (p = 0.02) subpopulations. Significantly increased expression of CD11c was associated with shorter symptom duration in both IM populations (rs = -0.38 and -0.44, p<0.05). Trend towards a decrease of intermediate monocytes and increase of classical monocytes during the initial treatment with GCS was demonstrated. Decrease of CD11c expression was associated with the daily GCS dose in all subpopulations (CM, IM-CD16 + or ++ and NCM: rs = -0.64, -0.55 or -0.50 and -0.40; p = 0.004, 0.08 or 0.02 and 0.09) at month three. No associations with disease activity or with MTX dosage were found. Conclusions: The expansion of intermediate monocyte subpopulations in ERA patients and enhancement of CD11c expression with reduction after three months of treatment with GCS suggest their possible role in the pathogenesis of RA at early stages of the disease. Acknowledgement: Institutional support MZČR0002372801